Józef Retinger – polski orędownik zjednoczenia Europy - Barabasz, Adam (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2008)
Józef Retinger was a great advocate of the continent’s unity. He had all the skills that are necessary in diplomacy: he spoke foreign languages and knew the customs of foreign countries; therefore he could always behave appropriately. He traveled extensively and thus he established numerous foreign contacts. He lacked only one feature: he could not speak in public and his sparkling personality did not come across during such performances. He was considered to be of gray eminence, a person who did not seek accolades. He would remain in the shadow of great personalities, but not of great events as he was more than their participant – he co-created them. He could always infect great personalities with an idea which would present in a dazzling way. Although he remained in exile until his death he was never indifferent to the fate of Poles under the yoke of Soviet communism.